A novel method to design biomimetic, 3D printable stochastic scaffolds with controlled porosity for bone tissue engineering. (August 2022) - Kanwar, Susheem; Al-Ketan, Oraib; Vijayavenkataraman, Sanjairaj
Graphical abstract: Highlights: A new simple mathematical design approach is proposedfor designing bone-mimicking stochastic scaffolds. Creation of stochastic scaffolds in a computationally inexpensive manner using simple level set equations. Ability to generate scaffolds with controllable topology and porosity, both locally and globally. Young's moduli of the 3D-printed 316L stochastic scaffolds are in the same range as that of trabecular bone (0.02 to 2 GPa). Stochastic scaffolds supported in vitro cell attachment and proliferation. Abstract: Periodic cellular materials such as body-centered cubic, face-centered cubic, and triply periodic minimal surfaces, have been used to construct scaffolds for bone tissue engineering. Their use is suboptimal for reasons like stress concentration at nodes, and/or poor anisotropy. Stochastic structures can mimic the bone microarchitecture with anisotropic mechanical properties. While several methods exist for generating stochastic structures, they face limitations like being computationally expensive, complex, or only applicable in specific cases. In this work, scaffolds are created using level set equations which permit spatially controllable porosity. A 3D volume is populated with random nodes, which segment the 3D volume into subdomains. Each subdomain is occupied with a basic architecture generated through level-set equations. All the architectures in the subdomains are then smoothly integrated at sub-domain boundaries to form the stochastic scaffold. Stainless steel stochastic scaffolds with porosities from 58% to 70% were fabricated and their mechanical characteristics, as well as cell viability, was assessed. Young's modulus of the scaffolds ranges from 0.02 to 2 GPa, in the same range as that of trabecular bone, thus, mitigating stress shielding. I n-vitro assay displayed a statistically significant osteoblast growth from Day 1 to Day 3 in 58%, 61%, and 64% porosity scaffolds.